Rekonstruksi Otoritas Fatwa di Era Digital - R, Randy; H, Herianti; Hasan, Hamzah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The digital transformation has significantly influenced the structure of religious authority in Islam, particularly in the domain of fatwas. In Indonesia, the emergence of popular religious figures on social media as primary sources of Islamic legal guidance indicates a shift from formal institutions to non-institutional actors. This phenomenon has led to the fragmentation of religious authority, undermining the legitimacy of fatwas and confusing the Muslim public. This study aims to analyze how the transformation of fatwa authority unfolds in the digital era, the extent to which collective ijtihad remains relevant in addressing this shift, and how contemporary Islamic legal thought—particularly that of Fazlur Rahman and Jasser Auda—can contribute to reframing fatwa authority today. Using a normative-qualitative approach and library research method, this study employs descriptive and comparative analysis of primary texts by key thinkers and official fatwa documents. The findings reveal that collective ijtihad is an essential epistemological strategy to restore balance amid the fragmented landscape of digital fatwas. Furthermore, Fazlur Rahman’s ethical-textual reinterpretation and Jasser Auda’s systems-based maqasid theory offer strong theoretical foundations for developing a participatory and adaptive model of fatwa authority. This study recommends an integrated approach between maqasid al-shariah and collective ijtihad as a constructive effort to reconstruct Islamic legal authority in a way that is both contextually grounded and epistemologically legitimate in the digital age.